MEMS-Based Integrated Navigation. - Aggarwal, Priyanka (Artech House, 2010)
Due to their micro-scale size and low power consumption, Microelectromechanical systems (MEMS) are now being utilized in a variety of fields. This leading-edge resource focuses on the application of MEMS inertial sensors to navigation systems. The book shows you how to minimize cost by adding and removing inertial sensors. Moreover, this practical reference provides you with various integration strategies with examples from real field tests. From an introduction to MEMS navigation related applications to special topics on Alignment for MEMS-Based Navigation to discussions on the Extended Kal.